Dinosaurs : fossils and feathers - Reed, M. K. (Science comics (First Second (Firm)), 2016)
Graphic novel detailing the work of early paleontologists as they search for the truth about the dinosaurs' extinction. Includes various scientists' adventures paired with facts, diagrams, and stories about dinosaurs in their prehistoric habitats.